Educational Strategies for Enhancing College Students’ Sports Awareness and Behaviour: A Study on Health Outcomes - Renyuan Zhang; Ali Khatibi; Jacquline Tham (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
At the university level, physical education represents both the culmination of an individual's structured physical training and a pivotal juncture for integration into social sporting circles. The manner in which students engage with physical activities during their academic tenure significantly influences their subsequent involvement in communal sports post-graduation. Consequently, it is imperative to examine the educational variables conducive to fostering positive sports consciousness and conduct among students. This study aims to scrutinize the correlation between collegiate sports awareness and behaviours to elucidate students' reasoned comprehension and acknowledgment of sports, alongside their current engagement in sporting endeavours. While sports awareness furnishes psychological underpinnings for sports-related conduct, it is not the sole determinant thereof. The holistic evaluation of collegiate sports awareness encompasses diverse facets such as health consciousness, aesthetic appreciation, emotional release, pursuit of excitement, social interactivity, and motivation for achievement. This research underscores the critical role of educational methodologies in shaping students' sports consciousness, augmenting their participation in sports, and cultivating wholesome lifestyles. By offering valuable insights into the structuring and execution of tertiary-level sports programs, this study contributes to the advancement of higher education sporting initiatives.